A newly isolated yeast as an expression host for recombinant lipase - Oslan, Siti Nurbaya; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha; Leow, Thean Chor; Sukamat, Hafizah; Basri, Mahiran (University of Wroclaw, 2015)
Pichia guilliermondii strain SO isolated from spoiled orange was developed for use as an alternative expression host by using Pichia pastoris as the model of the experiment. This is the first study to report on the capability of P. guilliermondii SO as a host to express thermostable T1 lipase from Geobacillus zalihae. Alcohol oxidase and formaldehyde dehydrogenase promoters were present in the yeast genome. Interestingly, the recombinant yeast [SO/pPICZαB/T1-2 (SO2)] took only 30 h to reach optimal production with minimal methanol induction [1.5% (v/v)] in YPTM medium, as compared to P. pastoris, which took longer to reach its optimal condition. The purification yield of the His-tagged fusion lipase was 68.58%, with specific activity of 194.58 U/mg. The optimum temperature was 65°C at pH 9 in glycine-NaOH buffer, and it was stable up to 70°C in a wide pH range from pH 5 to 12. In conclusion, a newly isolated yeast from spoiled orange has been proven suitable for use as an expression host.